Ghãtu: Femininity and Indigenous Aesthetics - Gurung, Raj Kumar (Bon Voyage, 2024)
Ghãtu is a cultural capital that explores the esteem of femininity and Indigenous aesthetics. Despite its aesthetic value, the main theme is sati custom, the over-exploitation of females. This tribal festival does not only belong to Gurung or Magar. Its horizon is up to Tamang, Dura, Darai, Baram and Aryal Kshetri in central and mid-western Nepal. All of them observe with almost similar methods and rituals. Except for Aryal Kshetri, other Indigenous groups claim that it is their hereditical cultural activity. The slow-motion meditative trance dance and melodious verses of songs represent the aesthetic beauty of Nepali folk music and folklore. The study concerns why ethnic groups adopted Ghãtu and the significance of implications of this cultural activity. The ethnic groups adopted it for its zeal for music. The study’s implication is to internalize this folk dance as a source of social integration, human relations, teamwork, music and folk literature, and a goldmine of cultural studies research works. Now, Ghãtu is a common cultural capital and a central stone of indigenous aesthetics and cultural studies. This study aims to project how this cultural activity represents a common cultural heritage like the Chhath festival. The findings of the study show that maintaining integral human relations is impossible until or unless society respects femininity and cultural values. So, culture, language, rites and rituals, and dresses are common, if the mass accepts it. Gender discrimination is another focal point, and there has not been research on how Ghãtu has been the archive and cultural heritage. The study employs document analysis and feminist theories.